Além da visão: mediações na experiência estética - Tomaz, Marina Vargas (2016)
How the multisensoriality and somatic use of the body can contribute to the artistic experience, either in the museum or in the classroom? This study aims to think the aesthetic experience, through a multisensory approach to visually impaired starting from the inclusion as equal rights and access to broad mediator feature. The multisensory mediation capabilities collaborate to improve the interaction of all, visionaries or not, against art and its processes, from the understanding of the body as an integrated, responsive whole.